2010
DOI: 10.1007/s13280-009-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Burning Water: A Comparative Analysis of the Energy Return on Water Invested

Abstract: While various energy-producing technologies have been analyzed to assess the amount of energy returned per unit of energy invested, this type of comprehensive and comparative approach has rarely been applied to other potentially limiting inputs such as water, land, and time. We assess the connection between water and energy production and conduct a comparative analysis for estimating the energy return on water invested (EROWI) for several renewable and non-renewable energy technologies using various Life Cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…GHG emissions, for example, are somewhere between 15% and 60% higher for gasoline and diesel produced from tar sands when compared to that produced from conventional petroleum [65,66]. Similarly, the water used per unit of energy produced is also much higher for most low EROI sources of energy [67]. Second, declining EROI increases the GERR.…”
Section: Implications For the Future Of Economic Growthmentioning
confidence: 99%
“…GHG emissions, for example, are somewhere between 15% and 60% higher for gasoline and diesel produced from tar sands when compared to that produced from conventional petroleum [65,66]. Similarly, the water used per unit of energy produced is also much higher for most low EROI sources of energy [67]. Second, declining EROI increases the GERR.…”
Section: Implications For the Future Of Economic Growthmentioning
confidence: 99%
“…The water requirement content (WRC) was defined by reviewing previous studies on the use of water for fossil energy production [31,32] and designated water consumption in this study. Table 1 shows the WRCs for fossil energy production.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…In this study, the blue component of water footprint is expressed in terms of the blue water consumption for fossil energy production in one year (unit: m 3 /year). In general, the water footprint can be evaluated by the bottom-up approach [24,31,36,37] or by the top-down approach [38][39][40]. The top-down approach can be categorized further into production and consumption-based approaches for the estimation of water footprint [40], and is usually used for environmental analyses by the economic input-output analysis [36].…”
Section: Estimation Of the Wfep And Wfesmentioning
confidence: 99%
“…The water consumption and water withdrawal include direct water inputs (e.g., water supplied to the growth volumes) and indirect water inputs (e.g., water used during nitrogen fertilizer production and electricity generation), thereby yielding a second-order water analysis. The energy return on water investment (EROWI) is a similar metric for evaluating water intensity [9,34] and can be calculated from the data in this study that are reported in Tables 3A and 4A. However, this metric does not consider the energy quality of the fuels produced, and therefore the and were used as the main metrics for evaluating water intensity in this study.…”
Section: Water Intensity Analysis Formulaementioning
confidence: 99%